2016
DOI: 10.1016/j.vaccine.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for measles in children aged 8 months–14 years in China after nationwide measles campaign: A multi-site case-control study, 2012–2013

Abstract: Introduction:Endemic measles persists in China, despite >95% reported coverage of two measles-containing vaccine doses and nationwide campaign that vaccinated more than 100 million children in 2010. In 2011, almost half of the 9943 measles cases in China occurred in children eligible for measles vaccination. We conducted a case-control study during 2012–2013 to identify risk factors for measles infection in children aged 8 months–14 years.Methods:Children with laboratory-confirmed measles were age- and neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
4
13
0
1
Order By: Relevance
“…This is in line with the finding of case control study conducted in Kabridehar town and Kabridehar district of Somali Regional State, Ethiopia, indicating that being vaccinated against measle vaccine is protective factor for contracting measle [ 15 ), 16 ]. Similarly, our finding is consistent with the case control study conducted in Uganda and China indicating unvaccinated against measles was responsible for most measles infection in children [ 18 ), 19 ]. This is due to the fact that vaccination against measles is vital for prevention of measles infection [ 1 - 3 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with the finding of case control study conducted in Kabridehar town and Kabridehar district of Somali Regional State, Ethiopia, indicating that being vaccinated against measle vaccine is protective factor for contracting measle [ 15 ), 16 ]. Similarly, our finding is consistent with the case control study conducted in Uganda and China indicating unvaccinated against measles was responsible for most measles infection in children [ 18 ), 19 ]. This is due to the fact that vaccination against measles is vital for prevention of measles infection [ 1 - 3 ].…”
Section: Discussionsupporting
confidence: 92%
“…Measles outbreaks occur when the accumulated number of susceptible individuals is greater than the critical number of susceptible individuals, or epidemic threshold for a given population [ 3 ]. Various literature on outbreak investigation showed that the possible factors for measles infections were being unvaccinated for measles, low immunization coverage, malnutrition, poor cold chain management and travel history to measle area, presence of measles case in neighbor or in the household and having contact with person with measles case [ 15 - 18 ]. Despite the increase in immunization coverage (administrative) of measles in the country, there was a widespread measles outbreak reported from different zones of Oromia region including Bale zone in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major findings of this study is that substantial increases in the proportions of infections were identified among both locals and migrants with no known immunization history of measles during 2009-2012 and 2013-2014. This is in accordance with the consensus that a lack of vaccination is the most significant risk factor for measles infection (World Health Organization, 2018; Centres for Disease Control and Protection (US), 2018a; Hao et al, 2016). In fact, the Guangzhou CDC has pointed out that there was a decrease in vaccine uptake among citizens, partially due to the negative reports and quackery about vaccines (Guangzhou Center for Disease Control and Prevention, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…MCVs used in China were found to be highly immunogenic in infants aged 8 months, and coadministration of Japanese encephalitis vaccine did not reduce measles seroconversion rates ( 6 ). In a Chinese study of risk factors for measles in children aged 8 months–14 years after a nationwide SIA, the estimated measles vaccine effectiveness among children was >95%, and being unvaccinated was the leading risk factor for infection ( 7 ). In addition, hospitals were important sites of measles virus transmission, and internal migration was associated with risk for measles acquisition ( 7 ).…”
Section: Discussionmentioning
confidence: 99%